Issues of Providing Ecological Sustainability in The New Uzbekistan - Oxunjonov Jamshidbek To’lqinjon o’g’li; Olimjonov Qobiljon Shuhrat o’g’li; Mamadaliyev Akbarali Asqarali o’g’li; Xayrullayev Xikmatullo Xabibulla o’g’li (Scientific Trends, 2025)
This article discusses the importance and shortcomings of the work being carried out in Uzbekistan and the world community to ensure environmental stability, as well as personal suggestions for ensuring environmental stability in Uzbekistan.
Keywords: ecology, environment, ecological stability, waste, enterprises, ecological safety, Aral Sea, UN, electricity.